Application of method of content analysis and perception survey in evaluating the effectiveness of planning system in managing housing supply - Rameli, Alias (2007)
Housing planning process is guided by several mechanisms in the planning system, from the preparation of structure and local plans to the development control process. In relation to the issues of overhang, unsold and oversupply, besides postulation that it is caused by housing market failures, there is also an argument which stated that this issues were also contributed by ineffectiveness of the current housing planning practice. In exploring its factuality, an empirical research has been conducted to explore both process and outcomes of development plans and development control in the Johor Bahru Conurbation area as a case study. The method of content analysis was used to analyse eight (N=8) structure plans, seven (N=7) local plans and eighty-two (n=82) housing development applications. Besides content analysis, a perception survey was also conducted using a structured questionnaire on sixty-one (N= 61) planners in the study area. To seek an insight views on the specific matters, an in-depth interview with the selected respondents will also be carried out after analysing data from the `pro-formas’ and questionnaire. This paper aims to discuss the research methodology which was applied in evaluating the effectiveness of planning system in managing housing supply. Prior to that, this paper will briefly discusses on housing development issues and major findings from literature study. Finally, some of the results from preliminary data analysis will also be discussed.